-3x-2=7x+4

Simple and best practice solution for -3x-2=7x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-2=7x+4 equation:


Simplifying
-3x + -2 = 7x + 4

Reorder the terms:
-2 + -3x = 7x + 4

Reorder the terms:
-2 + -3x = 4 + 7x

Solving
-2 + -3x = 4 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-2 + -3x + -7x = 4 + 7x + -7x

Combine like terms: -3x + -7x = -10x
-2 + -10x = 4 + 7x + -7x

Combine like terms: 7x + -7x = 0
-2 + -10x = 4 + 0
-2 + -10x = 4

Add '2' to each side of the equation.
-2 + 2 + -10x = 4 + 2

Combine like terms: -2 + 2 = 0
0 + -10x = 4 + 2
-10x = 4 + 2

Combine like terms: 4 + 2 = 6
-10x = 6

Divide each side by '-10'.
x = -0.6

Simplifying
x = -0.6

See similar equations:

| 100=2.5x | | 5z=60 | | 1.6q-3.5-5.2q=-4.6q-5.4 | | 4x+10=x+3(3x+3)+1 | | 12x^2+41x+24=0 | | 5x+29y=-19 | | 2(n+2)=3n+9 | | x*6+47=x*11-8 | | x^3-70x^2+1500x-10800=0 | | 5(y-1)=7(3+y) | | 18x^2-9x-20=0 | | b^2+3=5b-3 | | 58-6x=3x+19 | | x^2+36=100 | | 8-2a=2 | | -3-2(y+4)=3y-(4y-5) | | 12x^2+43x+36=0 | | 5(2x+n)=2(n-1) | | 47=-62 | | 10x+6x= | | 29+18=-59-3 | | 3x=5y+2 | | 3(2x-1)=11-x | | 4y-4=6-7y | | 18x-3=51 | | 18y=15(y-8) | | -4x-12=13+x | | 5m+8-2m=17+4m-3 | | 5y=x+17 | | 6m-12m=1-4 | | 40x+780=70x+1230 | | 8y-6(3y-7)=0 |

Equations solver categories